The Influence of Leadership and Work Discipline on PT Ammana Fintek Syariah Employee Performance - Zainuri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to test leadership, whether work discipline affects employee performance, namely the performance of PT Ammana Fintek Syariah employees. The research method uses a quantitative approach, by collecting data using primary data, secondary data for Personnel Managers and library research. Primary data uses all employees at PT Ammana Fintek Syariah as many as 30 respondents. Data collection techniques using interviews and questionnaire instruments. The questionnaire survey instrument was delivered to employees of PT Ammana Fintek Syariah. Data were analyzed using the SPSS model to test the significance of the influence of leadership and work discipline on employee performance. The results of the study show that leadership, work discipline has a significant positive effect on employee performance, both partially and simultaneously. Leadership as the most important factor influencing employee performance. The managerial implication is that an organization or leader must develop a harmonious work culture and work discipline for employees to achieve their best performance